The method of selection of the setpoint high speed feeder switch of 3,3kV DC with microprocessor-based protection systems - Mykhalichenko, P. Ye. (Science and Transport Progress, 2010)
In the article a new procedure of choice of minimum current jump for action of fast-acting switches of 3.3 kV DC traction substations intended for the use in the microprocessor protection system of feeders is described. This procedure is more perfect than existing one on the current increment and uses the results of mathematical simulation of the traction electric supply system.